Synthesis of Feed-Grade Tribasic Copper Chloride with Alkaline Etching Waste Liquor after the Co-precipitation of Lead and Arsenic - Xu, H.B.; Fan, H.T.; Jiang, X.J.; Sun, T. (Asian Journal of Chemistry, 2011)
A new and effective synthesis of feed-grade tribasic copper chloride was developed using alkaline etching waste liquor. The lead and arsenic in alkaline etching waste liquor were directly removed by co-precipitation with mixed nascent calcium carbonate-ferric hydroxide. The co-precipitation conditions, such as the settling time, temperature, pH and the amount of carrier elements, were investigated. The obtained tribasic copper chloride powder was characterized by XRD and electron microscopy. Results indicated that for 1 L alkaline etching waste liquor at 40 ºC and a pH of 8.0, addition of 2.3 g of ferric chloride, 10 g of calcium chloride and 10 g of sodium carbonate led to removal rates for lead and arsenic of 92.4 and 94.6 %, respectively. The contents of lead and arsenic of tribasic copper chloride were 7.4 and 3.5 mg/kg, respectively. Results showed that the synthetic tribasic copper chloride can be used as the feed additive.